A systematic review on innovations in computer aided design in engineering education - Margarita F. Murillo Manrique; Jorge Augusto Sánchez Ayte (Institute of Advanced Engineering and Science, 2025)
curricula up-to-date with advanced computer-aided design (CAD) technologies to understand their practical application in various industrial and research contexts. Given this need, a systematic review was proposed following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) method to evaluate the most recent innovations in CAD systems and their effective application in engineering education. The results reveal that emerging technologies such as real-time virtual collaboration, 3D design, and virtual reality are being incorporated into educational environments, significantly enhancing students’ technical and collaborative skills. The research concludes that these technologies not only reconfigure engineering education, emphasizing a practical and updated approach, but also facilitate a more interactive and effective learning experience. This study highlights the urgent need to adapt educational programs to incorporate these innovations, thus ensuring that future engineers are better prepared to face the challenges of modern industry.